The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1021/mp4000053
|View full text |Cite
|
Sign up to set email alerts
|

Preventative Vaccine-Loaded Mannosylated Chitosan Nanoparticles Intended for Nasal Mucosal Delivery Enhance Immune Responses and Potent Tumor Immunity

Abstract: Chitosan (CS) has been extensively used as a protein drug and gene delivery carrier, but its delivery efficiency is unsatisfactory. In this study, a mannose ligand was used to modify CS, which could enhance the delivery efficiency of CS via mannose receptor-mediated endocytosis. A preventative anti-GRP DNA vaccine (pCR3.1-VS-HSP65-TP-GRP6-M2, pGRP) was condensed with mannosylated chitosan (MCS) to form MCS/pGRP nanoparticles. Nanoparticles were intranasally administered in a subcutaneous mice prostate carcinom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(40 citation statements)
references
References 39 publications
1
39
0
Order By: Relevance
“…More recently, mannosylated Ch nanoparticles have been administered by the nasal mucosa route to elicit serum anti-GFP IgG anitibodies and inhibit the growth of gastrin-releasing peptide (GRP) dependent tumor cells. The results confirmed that these Ch based carriers are feasible in DNA vaccine delivery and they offer a possibility for efficient tumor immunotherapy [94].…”
Section: Other Delivery Routessupporting
confidence: 66%
“…More recently, mannosylated Ch nanoparticles have been administered by the nasal mucosa route to elicit serum anti-GFP IgG anitibodies and inhibit the growth of gastrin-releasing peptide (GRP) dependent tumor cells. The results confirmed that these Ch based carriers are feasible in DNA vaccine delivery and they offer a possibility for efficient tumor immunotherapy [94].…”
Section: Other Delivery Routessupporting
confidence: 66%
“…Targeting the mannose receptor, a C-type lectin, showed that mannosylation provided an efficient strategy to improve antigen uptake, processing, and presentation. Mannosylation enhanced uptake of VLPs by antigen-presenting cells (38), and also enhanced the cell-mediated and humoral immunogenicity of immunogens (40,(45)(46)(47). Mannosylated solid lipid nanoparticles loaded with HBsAg induced stronger cellular responses than nanoparticles devoid of mannose (48).…”
mentioning
confidence: 99%
“…Mannose functionalization of chitosan increases nanoparticle association with APCs and increases internalization via mannose receptor-mediated endocytosis. [46][47][48] Layek et al 49 developed an L-phenylalanine-modified chitosan for increased adsorptive endocytosis and intracellular dissociation of DNA, further functionalized with mannose for APC-specific targeting (Man-CS-Phe/DNA). Following intradermal delivery of Man-CS-Phe/DNA complexes encoding hepatitis B surface antigen (HBsAg) to mice, high anti-HBsAg titers were observed for up to six weeks, as well as increased lymphocyte proliferation and increased IL-4 and IFN-g production.…”
Section: Natural Polymersmentioning
confidence: 99%